CD11c-expressing cells affect Treg behavior in the meninges during CNS infection() - O’Brien, Carleigh A. (J Immunol, 2017)
Treg cells play an important role in the CNS during multiple infections as well as autoimmune inflammation, but the behavior of this cell type in the CNS has not been explored. In mice, infection with Toxoplasma gondii leads to a Th1-polarized parasite-specific effector T cell response in the brain. Similarly, the Treg cells in the CNS during T. gondii infection are Th1-polarized, exemplified by T-bet, CXCR3, and IFN-γ expression. Unlike effector CD4(+) T cells, an MHC Class II tetramer reagent specific for T. gondii did not recognize Treg cells isolated from the CNS. Likewise, TCR sequencing revealed minimal overlap in TCR sequence between effector and regulatory T cells in the CNS. Whereas effector T cells are found in the brain parenchyma where parasites are present, Treg cells were restricted to the meninges and perivascular spaces. The use of intravital imaging revealed that activated CD4(+) T cells within the meninges were highly migratory, while Treg cells moved more slowly and were found in close association with CD11c(+) cells. To test whether the behavior of Tregs in the meninges is influenced by interactions with CD11c(+) cells, mice were treated with anti-LFA-1 antibodies to reduce the number of CD11c(+) cells in this space. The anti-LFA-1 treatment led to fewer contacts between Tregs and the remaining CD11c(+) cells and increased the speed of Treg cell migration. These data suggest that Treg cells are anatomically restricted within the CNS and the interaction with CD11c(+) populations regulates their local behavior during T. gondii infection.